Alternatif Kebijakan Pertanian dalam Menghadapi Otonomi Desa di Kabupaten Tabanan - I Putu Dharmanu Yudartha (Research and Development Agency Ministry of Home Affairs, 2017)
The implementation of village autonomy requires the village government exploring the potential in the village into the leading sector. The agricultural sector becomes one of the ideal potentials in the Tabanan District to support national development. Currently the village government has the authority to assist local government duties. Therefore, development in the village should optimize the agricultural sector. The problems facing the agricultural sector in Tabanan are poorness, the absence of industrial processed agricultural products, and conversion of agricultural land.This paper aims to discuss and analyze the challenges and obstacles related to agricultural sector policy in the context of village autonomy with descriptive approach. Analysis carried out by combining theoretical and case or phenomenon that occurs later will be formulated into a form of public policy of the agricultural sector in the face of village autonomy. Village autonomy is the central government’s effort to restore the role of the village as a leader in national development. Village is identical as a food barn; this role is what wants to be restored so that the development pattern becomes bottom up. To support and realize the role of villages, especially in the agricultural sector, alternative policy is needed. The policy alternatives referred to are as follows; Empowerment of the rural sector, subsidies on agricultural input, agricultural output policies and the incorporation of previous policies.